TERRITORIAL BRANDING AS A MARKETING INSTRUMENT IN THE TOURISM INDUSTRY - Murodova Nargiza , Utkirovna (THE INNOVATION ECONOMY, 2025)
Place branding as an important marketing tool in the tourism industry has become a subject of growing interest among researchers and practitioners. This paper analyzes the role of branding as a key element of the marketing strategy for promoting tourist destinations. Using the example of Samarkand, it is shown how effective positioning of a region through cultural heritage, visual elements and digital platforms helps to form a unique image and attract tourists. The study revealed the importance of integrating historical and cultural factors, verbal and visual aspects of the brand, as well as digital technologies in the process of creating a successful place brand. As a result of the analysis, recommendations were proposed to improve tourism branding and increase the competitiveness of the region in the global market